Treatment options for haemophilic arthropathy of the elbow after failed conservative therapy - Strauss, A. C.; Goldmann, G.; Ezziddin, S.; Placzek, R.; Müller, M. C.; Pflugmacher, R.; Oldenburg, J.; Pennekamp, P. H. (Hämostaseologie, 2014)
After ankle and knee, the elbow is the most frequent joint affected by haemophilic arthropathy. objective: The objective of this retrospective single centre study is to evaluate the results of treatment of elbow arthropathy after failed conservative therapy. Patients, methods: In 21 consecutive patients, 11 radiosyn-oviortheses (RSO), four arthroscopic and six open synovectomies were performed, among them four with additional resection of the radial head. The mean duration of follow-up was 4.8 (RSO) and 5.3 years (surgery), respectively. Pain status (visual analogue scale, VAS), bleeding frequency, range of motion (ROM) as well as patient satisfaction were evaluated. Results: Both, RSO and surgical synovectomy, achieved a significant reduction of pain and bleeding frequency (p < 0.05). Surgical synovectomies were associated with a marked yet not statistically significant increase of postoperative ROM. Radial head resection improved forearm rotation in all cases. No complications occurred. 20 out of 21 patients were satisfied or highly satisfied with the result of the treatment and would undergo the respective procedure again. Conclusion: Due to the effectiveness and safety RSO is considered to be the primary treatment option in haemophilic arthropathy of the elbow after failed conservative therapy. Arthroscopic synovectomy should be considered if RSO shows inadequate effect or in the presence of contraindications. Open synovectomy with resection of the radial head yields good results in the case of advanced arthropathy with radial head impingement.
Keywords: Elbow; haemophilia; arthropathy; treatment